Основні засади використання педагогічної технології взаємодії дошкільного навчального закладу і сім’ї у формування здорової особистості дитини - Семенова, Наталя; Гречук, Любов; Ясінська, Наталя; Semenova, N.; Grechuk, L.; Yasinskaya, N. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті представлено психолого-педагогічні основи процесу формування здорової особистості дитини 6-го року життя у процесі педагогічної взаємодії дошкільного навчального закладу і сім’ї та дано оцінку його сучасному стану. Уточнено сутність понять «здорова особистість», «здорова особистість дитини 6-го року життя», «формування здорової особистості дитини 6-го року життя», «взаємодія дошкільного навчального закладу і сім’ї». The article presents the psychological-pedagogical foundations for forming a healthy personality of children between 5 and 6 years of age in the process of pedagogical interaction between preschool education institutions and families and offers an evaluation of the current state of affairs in the area. The concepts “healthy personality”, “healthy personality of a child between 5 and 6 years of age”, “forming a healthy personality of a child between 5 and 6 years of age” and “interaction between preschool education institutions and families” have been defined more precisely. The author has developed a system of criteria and indices to evaluate healthy personality levels among children between 5 and 6 years of age. An experimental pedagogical technology for forming a healthy personality among children between 5 and 6 years of age in the process of interaction between preschool education institutions and families has been developed and tested.
Basic principles on the use of pedagogical technology of interaction of preschool educational institution and family in the formation of healthy personality of the child
Keywords: здорова особистість; формування здорової особистості дитини 6-го року життя; взаємодія дошкільного навчального закладу і сім’ї; педагогічна технологія; healthy personality; forming a healthy personality of children between 5 and 6 years of age; interaction between preschool education institutions and families; pedagogical technology